Masticatory Capacity and Mortality: The Preventive and Clinical Investigation Center (IPC) Cohort Study. (February 2020) - Darnaud, C.; Thomas, F.; Danchin, N.; Boutouyrie, P.; Bouchard, P.
Poor oral health (OH) has been associated with mortality, but the association between OH components and mortality remains imprecise. The present observational study aimed to investigate if there is an association between oral masticatory efficiency and cardiovascular (CV) mortality in a large French subject cohort. The study was based on a cohort of 85, 830 subjects aged between 16 and 94 y at recruitment. The follow-up extended from 2001 to 2014 and the mean follow-up was 8.06 ± 2.73 y. The number of deaths totaled 1, 670. Full-mouth examinations were performed. Dental plaque, dental calculus, gingival inflammation, missing teeth, and masticatory units were recorded. Masticatory units represent the number of natural or prosthetic opposing premolars and molar pairs and can be considered an accurate indicator for masticatory efficiency. Causes of death were ascertained from death certificates. Cox regression analyses were used to calculate hazard ratios (HRs). In the fully adjusted model, the number of masticatory units <5 is associated with an HR of 1.72 (95% confidence interval [CI], 1.54 to 1.91) for all-cause mortality, HR of 1.41 (95% CI, 1.01 to 1.99) for CV mortality, HR of 1.76 (95% CI, 1.44 to 2.15) for cancer mortality, and HR of 1.85 (95% CI, 1.55 to 2.20) for non-CV and noncancer mortality. Significant statistical associations with the other oral variables were also found for all-cause mortality, cancer mortality, and non-CV and noncancer mortality in the adjusted models. Our study indicates that after full adjustment, all oral parameters are associated with all-cause, cancer, and non-CV and noncancer mortality. However, the low number of masticatory units is associated with an increased risk of CV mortality. We highlight the association of masticatory units and CV mortality.